Effects of dietary vitamin E and vitamin C supplementation on the level of α-tocopherol and L-ascorbic acid in muscle and on the antioxidative status and meat quality of pigs - R. Lahučký; I. Bahelka; K. Novotná; K. Vašíčková (Czech Journal of Animal Science, 2005)
In total thirty pigs (Slovak Meaty) defined by DNA based test as not susceptible to malignant hyperthermia (non-mutant on RYR1) were used in the experiment. Treatment consisted in supplementation of vitamin E (500 mg α-tocopherol/kg diet as α-tocopherol acetate) (group E) and the same doses of vitamin E plus vitamin C (200 mg L-ascorbic acid/kg diet) (group E + C) to finishing pigs for the last 30 days before slaughter. The higher dietary vitamin E level resulted in higher levels of α-tocopherol in fresh (24 h), chill-stored (5 days, 4°C), chill-stored and cooked (80°C) and frozen meat (3 months, -25°C), (P < 0.05). Higher dietary vitamin C resulted in higher levels L-ascorbic acid in fresh and chill-stored meat (P < 0.05) but no significant differences vs. control pigs were observed in cooked and frozen meats. Supplementation with vitamins E and C (group E + C) had positive effects on pH (45 min) (P = 0.06) and on drip loss (P < 0.05) values as compared to control group. The rate of oxidation (malondialdehyde-MDA production) by stimulation with Fe2+/ascorbate (incubation of muscle LD for 0 and 30 min) was higher in control group as compared to both experimental groups (P < 0.05). Positive effects of vitamin E on oxidative stability measured as thiobarbituric acid reactive substances (TBARS, MDA) were observed mainly in chill-stored meat (P < 0.05). Using TBARS method, no additional effect of vitamin C on oxidative stability of fresh, chill-stored, cooked and frozen meat was found. In conclusion, supplementation of the combination of vitamin E (500 mg α-tocopherol/kg diet) and vitamin C (200 mg L-ascorbic acid/kg diet) for 30 days before slaughter improved meat quality values (drip loss, pH), however, it seems to depend on the genetic background of animals (occurrence of mutation on RYR1). Oxidative stability of meat lipids measured as TBARS value can be improved by vitamin E supplementation to feed.